Processed Fluid Chemistry Data from the Ross Sea acquired during the Nathaniel B. Palmer expedition NBP0601 - DiTullio, Giacomo; Smith, Walker (IEDA: US Antarctic Program Data Center, 2020)
This data set was acquired with a Niskin Bottle Fluid Sampler during Nathaniel B. Palmer expedition NBP0601 conducted in 2005 (Chief Scientist: Dr. Giacomo DiTullio). The data files are in XLS format and include Fluid Chemistry data that have been processed. The data was acquired as part of the project called Interaction of iron, light and CO2 on phytoplankton community dynamics in the Ross Sea. Funding was provided by NSF grants: ANT03-38097, ANT03-38157, ANT03-38164, and ANT03-38350.